Mycorrhizosphere Bacteria, Rahnella sp. HPDA25, Promotes the Growth of Armillaria gallica and Its Parasitic Host Gastrodia elata - Liu, Tianrui; Hua, Zhongyi; Han, Pengjie; Zhao, Yuyang; Zhou, Junhui; Jin, Yan; Li, Xiaolin; Huang, Luqi; Yuan, Yuan (Frontiers in Microbiology, 2022)
Plant-fungal interaction is extremely crucial in orchid mycorrhizal symbiosis. Whether the microbiome community structure and function in myco-heterotrophic symbiosis in different ecological environments affect the growth of orchid and mycorrhizal fungi remains unknown. Here, we cultivated completely heterotrophic Gastrodia elata in woodland or farmland and observed a greater yield and tuber size of woodland-cultivated G. elata. The relative abundance of genus Rahnella was 22.84- and 122.25-fold higher in woodland-cultivated and farmland-cultivated soil samples than those of uncultivated soil samples, respectively. Three strains of Rahnella spp. (HPDA25, SBD3 and SBD11) were isolated from mycorrhizosphere soil samples. Indole-3-acetic acid (IAA) was detected in HPDA25 fermentation solution using UPLC-QQQ-MS. Co-culturing with the stain HPDA25 and IAA increased rhizomorph branching, fresh weight of rhizomorphs, growth rate, and extracellular laccase activity of A. gallica compared with A. gallica cultured alone. The results of RNA-seq and RT-PCR show that up-regulated expression level of hydrophobin, SUR7/PalI family, pectin methylesterase, and down-regulated expression level of glycolysis-related genes in A. gallica co-culturing with the stain HPDA25. Furthermore, co-culturing with the stain HPDA25, A. gallica and G. elata promote the growth of A. gallica and G. elata, and enhance the tuber size of G. elata. These results in this study provide new insights into orchid mycorrhizal symbiosis and G. elatacultivation.